Epidemiology of Schistosoma and Gastrointestinal Parasites in Goats: A Slaughterhouse-Based Study from Malwa Region, Madhya Pradesh, India - Solanki, Himanshi; Agrawal, Vivek; Shakya, Mukesh; Kumar Jaiswal, Amit; S Choudhary, Nidhi; Jain, Rupesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Gastrointestinal (GI) parasitic infections, including those caused by Schistosoma species, represent a major constraint to goat health and productivity. This research aimed to elucidate the prevalence and epidemiological dynamics of Schistosoma and other GI parasites in goats slaughtered in the Malwa region of Madhya Pradesh, India. A total of 312 fecal and mesenteric tissue samples were systematically collected from goats at the Mhow Cantonment Slaughterhouse during the summer and monsoon seasons of 2024. Diagnostic assessments were performed using flotation, sedimentation, and McMaster techniques, supplemented by morphological identification of Schistosoma worms and eggs. The findings revealed a significantly higher prevalence of GI parasites during the monsoon season (p<0.05), with Eimeria spp. (63.14%) and strongyles (59.29%) predominating. Schistosoma indicum was detected in 1.60% of the sampled goats. Males demonstrated a markedly higher prevalence of parasitism (70.08%) compared to females (53.84%, p<0.05), while adults (66.66%) exhibited a higher infection rate than kids (37.5%, p<0.01). Breed-specific differences were also observed, with Jamunapari goats exhibiting the highest prevalence (71.60%), followed by Sirohi, Barbari, and Beetal breeds. The highest parasite intensities were recorded for Eimeria spp. (2377 ± 226 EPG) and strongyles (2329 ± 230 EPG), with comparatively lower counts for Trichuris, Fasciola, and Schistosoma spp. The study highlights the significant burden of GI parasitism in goats and underscores the need for targeted and season-specific control strategies to enhance animal health and productivity in the Malwa region.